How do you simplify #-(3a^6 b^4)^3#?

1 Answer
Jun 19, 2018

Answer:

See a solution process below:

Explanation:

First, use this rule for exponents to rewrite the #3# term:

#a = a^color(red)(1)#

#-(3a^6b^4)^3 => -(3^color(red)(1)a^6b^4)^3#

Next, use this rule to eliminate the outer exponent:

#(x^color(red)(a))^color(blue)(b) = x^(color(red)(a) xx color(blue)(b))#

#-(3^color(red)(1)a^color(red)(6)b^color(red)(4))^color(blue)(3) => -3^(color(red)(1)xxcolor(blue)(3))a^(color(red)(6)xxcolor(blue)(3))b^(color(red)(4)xxcolor(blue)(3)) => -3^3a^18b^12 => -27a^18b^12#